1997
DOI: 10.1021/jm9606756
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Pharmacological Characterization of (+)-2-Aminobicyclo[3.1.0]hexane-2,6-dicarboxylic Acid (LY354740):  A Potent, Selective, and Orally Active Group 2 Metabotropic Glutamate Receptor Agonist Possessing Anticonvulsant and Anxiolytic Properties

Abstract: 2-Aminobicyclo[3.1.0]hexane-2,6-dicarboxylic acid (9) was designed as a conformationally constrained analog of glutamic acid. For 9, the key torsion angles (tau 1 and tau 2) which determine the relative positions of the alpha-amino acid and distal carboxyl functionalities are constrained where tau 1 = 166.9 degrees or 202 degrees and tau 2 = 156 degrees, respectively. We hypothesized that 9 would closely approximate the proposed bioactive conformation of glutamate when acting at group 2 metabotropic glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
238
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 391 publications
(247 citation statements)
references
References 41 publications
9
238
0
Order By: Relevance
“…Effect of LY354740 (20 mg/kg, s.c.) on EPM Behavior LY354740 (20 mg/kg, s.c.) administered 30 min prior to the EPM test significantly increased anxiolytic-like behavior in the outbred ICR:CD-1 strain of mice, which is consistent with previous reports using other mouse strains (Monn et al, 1997;Helton et al, 1998). LY354740-treated mice spent significantly more time in the open arms and entered the open arms more frequently than saline-treated mice ( Figure 2a and b).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Effect of LY354740 (20 mg/kg, s.c.) on EPM Behavior LY354740 (20 mg/kg, s.c.) administered 30 min prior to the EPM test significantly increased anxiolytic-like behavior in the outbred ICR:CD-1 strain of mice, which is consistent with previous reports using other mouse strains (Monn et al, 1997;Helton et al, 1998). LY354740-treated mice spent significantly more time in the open arms and entered the open arms more frequently than saline-treated mice ( Figure 2a and b).…”
Section: Resultssupporting
confidence: 92%
“…(1S,2S,5R,6S)-2-aminobicyclo [3.1.0]hexane-2,6-dicarboxylic acid (LY354740) is a selective and potent agonist for mGlu2 and mGlu3 receptors (Monn et al, 1997). It activates human cloned mGlu2 and mGlu3 receptors in non-neuronal cells with EC 50 values of 5 and 24 nM, respectively, while EC 50 values for other mGlu receptors were 36 mM (mGlu8) or higher (EC 50 4100 mM for mGlu1, 5, 4, 7) (reviewed by Schoepp et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LY354740 has evidenced activity in a number of rodent stress and anxiety models, including fear-potentiated startle, elevated plus maze, lactate-induced panic, and stress-induced hyperthermia (Walker et al, 2002;Tizzano et al, 2002;Monn et al, 1997;Shekhar and Keim, 2000;Spooren et al, 2002). Importantly, the effects of LY354740 occur at doses that are not associated with psychomotor impairment, which is common with benzodiazepine pharmacology (Helton et al, 1998;Tizzano et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies conducted by many authors have shown that the increase in glutamatergic activity leads to anxiety; conversely, inhibition of this transmission produces antianxiety effects Pilc et al, 2000;Tatarczynska et al, 2001;Helton et al, 1998;Monn et al, 1997;Dunn et al, 1989). L-SOP and L-CCG-I are agonists of group III mGluRs and it is generally accepted that the activation of these receptors results, via a presynaptic mechanisms, in a modulatory inhibition of Glu transmission (Gereau and Conn, 1995;Vignes et al, 1995).…”
Section: Anxiolytic Effect Of Intrahippocampal Mglur Ligands and Npy mentioning
confidence: 99%